Cardiovascular disease risk among Australian unpaid carers – A survival analysis using 15 waves of the HILDA survey - Ameer Lambrias; Yamna Taouk; Jennifer Ervin; Tania King (PLoS ONE, 2025)
Background Engaging in chronically stressful behaviours has been hypothesised to increase the risk of experiencing cardiovascular disease (CVD). Providing unpaid care is known to be a stressful activity, but it is not clear whether this caregiving is associated with CVD. This study filled a gap in the existing literature by examining the association between providing unpaid care and incident cardiovascular disease among a nationally representative sample of Australian adults. Methods 11,123 adult participants aged over 18 years from the Household Income and Labour Dynamics in Australia (HILDA) survey were followed for up to 14 years from baseline (2003) until 2017. Gender-stratified survival analysis models used self-reported caregiving and heart disease statuses as well as time-varying covariates, to assess the association between providing high-intensity or low-intensity unpaid care (to an elderly or disabled relative) and incident CVD in comparison with a non-caregiving control. Results Among females, there was weak evidence that CVD was associated with high-intensity unpaid care (HR = 1.27, 95% CI = [0.83, 1.95]) and no evidence for low-intensity unpaid care (HR = 0.79, 95% CI = [0.50, 1.26]) in comparison with non-carers after adjusting for confounders. There was no association between caregiving and incident CVD for high-intensity (HR = 0.82, 95% CI = [0.47, 1.42]) or low-intensity (HR = 0.84, 95% CI = [0.55, 1.28]) caregiving males in the adjusted models. Conclusions These findings do not provide strong evidence to reject the null hypothesis that providing unpaid care does not increase risk of developing CVD in the Australian population. Given that these findings are somewhat inconsistent with the extant literature from other populations, further research is necessary, both in Australia and internationally, to build on the findings of this study and improve understanding of the nature of the association between caregiving and incident CVD.